2006
DOI: 10.3892/ijo.28.2.399
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signature induced by pregnancy in the human breast

Abstract: We have postulated that the lifetime protective effect of an early pregnancy against breast cancer is due to the complete differentiation of the mammary gland characterized by a specific genomic signature imprinted by the physiological process of pregnancy. For demonstrating this hypothesis we compared the genomic profile of the epithelium and the stroma of normal breast tissues from reduction mammoplasties performed in postmenopausal parous and nulliparous women. The epithelium and the stroma were separately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 35 publications
1
61
0
1
Order By: Relevance
“…Cluster C represents differentiation-associated genes whose level of expression continuously and progressively increases with time of pregnancy, reaching their highest levels between 21 and 42 days postpartum, and cluster D comprises genes that are up-regulated around the 15th day of pregnancy and become progressively down-regulated from the end of pregnancy until the 42nd day postpartum (25). These observations confirm at genomic level our previous morphologic and physiologic findings indicating that temporal and sequential changes have to occur in the development of the mammary gland for accomplishing a protective degree of differentiation (11,12,(25)(26)(27)(28). The importance of identifying a specific signature by 42 days postpartum is highlighted by the observations that administration of the polycyclic hydrocarbon 7,12-dimethylbenz(a)anthracene to parous rats results in a markedly reduced tumorigenic response, supporting the concept that the differentiation induced by pregnancy shifts the susceptible ''intermediate cells '' that originate mammary cancer in the terminal end buds of the virginal gland (5, 10) to transformation-resistant cells (11,12).…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Cluster C represents differentiation-associated genes whose level of expression continuously and progressively increases with time of pregnancy, reaching their highest levels between 21 and 42 days postpartum, and cluster D comprises genes that are up-regulated around the 15th day of pregnancy and become progressively down-regulated from the end of pregnancy until the 42nd day postpartum (25). These observations confirm at genomic level our previous morphologic and physiologic findings indicating that temporal and sequential changes have to occur in the development of the mammary gland for accomplishing a protective degree of differentiation (11,12,(25)(26)(27)(28). The importance of identifying a specific signature by 42 days postpartum is highlighted by the observations that administration of the polycyclic hydrocarbon 7,12-dimethylbenz(a)anthracene to parous rats results in a markedly reduced tumorigenic response, supporting the concept that the differentiation induced by pregnancy shifts the susceptible ''intermediate cells '' that originate mammary cancer in the terminal end buds of the virginal gland (5, 10) to transformation-resistant cells (11,12).…”
Section: Introductionsupporting
confidence: 79%
“…Nevertheless, the final molecular mechanisms by which these transcription factors regulate the differentiation of the parous breast epithelium need further investigation. Transcription factors also associated to coactivators and chromatin remodeling, such PCAF, which have previously found to be significantly up-regulated in breast epithelial cells of parous women (6,(25)(26)(27), seem to play Figure 1. Unsupervised hierarchical clustering analysis using the expression profiles of 2,541 globally varying genes across the nulliparous and parous data sets representing parous controls ( ), parous cases ( ), nulliparous controls ( ), and nulliparous cases ( ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In perhaps the only previous study to address the effect of parity on gene expression profiles in the normal breast, Russo and coworkers applied cDNA microarrays to ethanolfixed tissue obtained from postmenopausal women (34)(35)(36). In this discovery effort, a large number of genes were found to be differentially expressed between parous and nulliparous women, including a number of immune-related genes that were upregulated in the parous group.…”
Section: Discussionmentioning
confidence: 99%
“…When the film is lifted, the 'captured' cells can be transferred directly into a digestion buffer for extraction of nucleic acids for subsequent analysis (16). Several studies have shown the genomic expression from isolated tumor breast cells using LCM (17)(18)(19)(20)(21)(22)(23), however very few publications (20)(21)(22)(23)(24) show the successful gene expression study using microarrays technologies from laser captured breast epithelial cells from paraffin-embeddednormal breast tissue. Another objective of the present work is to compare two different methods of RNA amplification, the linear one already described in the literature (25,26) and a PCR based method developed in our laboratory.…”
Section: Introductionmentioning
confidence: 99%